INTERNATIONAL CONFERENCE "I EURASIAN SEMINAR ON THE PROTECTION OF THE RIGHTS OF CITIZENS» The city of VALMONTONE (ITALY) (Journal of actual problems of jurisprudence, 2019)
In the final discussion of the results of the seminar, recommendations on the establishment ofThe Eurasian coordinating Council of ombudsmen, through which to exchangeexperience, theoretical development and analysis of practical activities of defenders of the rights of citizens.There was General agreement on the need for close international cooperationnational human rights institutions in the field of monitoring the observance of the rights of citizens andapplication of generally recognized norms and standards in this field.